2021
DOI: 10.3390/ijerph18062892
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Account of Young People’s Experiences Seeking Care from Emergency Departments for Self-Harm

Abstract: Many young people who engage in self-harm do not seek help from health services. For those that do, emergency departments (EDs) are a key point of contact. Substantial gaps remain in current knowledge related to young consumers’ experiences and views on optimal treatment of self-harm in the ED. In this study, semi-structured interviews were conducted with thirteen young people (Mage = 21.2 years), who were engaged with care at headspace early intervention centers and had presented to an ED with a self-inflicte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 78 publications
5
38
1
1
Order By: Relevance
“…9,16 This fits with recent findings from the perspective of young people in Australia, who emphasised how emergency department care was countertherapeutic. 10 In line with previous findings about what matters from the perspective of young people and adults seeking help, we found that helpful treatment in the emergency department is being respected, believed and taken seriously. 10,17 The therapeutic value of having someone to talk to was emphasised by patients and carers alike – which is essential for people to fully disclose their experiences to practitioners and for practitioners to conduct a valid risk assessment.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…9,16 This fits with recent findings from the perspective of young people in Australia, who emphasised how emergency department care was countertherapeutic. 10 In line with previous findings about what matters from the perspective of young people and adults seeking help, we found that helpful treatment in the emergency department is being respected, believed and taken seriously. 10,17 The therapeutic value of having someone to talk to was emphasised by patients and carers alike – which is essential for people to fully disclose their experiences to practitioners and for practitioners to conduct a valid risk assessment.…”
Section: Discussionsupporting
confidence: 90%
“…10 In line with previous findings about what matters from the perspective of young people and adults seeking help, we found that helpful treatment in the emergency department is being respected, believed and taken seriously. 10,17 The therapeutic value of having someone to talk to was emphasised by patients and carers alike – which is essential for people to fully disclose their experiences to practitioners and for practitioners to conduct a valid risk assessment. 18 A human connection was considered most important for patients, where a therapeutic encounter could instil hope at a time when life does not feel worth living, and can potentially be life-saving, as reported in previous studies.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Experiences of the ED can be overwhelmingly negative, and staff can be dismissive, disinterested and lacking in knowledge [38]. This was reiterated by the young people in this study, especially those who had made repeat presentations to EDs.…”
Section: Young People's Experiences Of Staff Attitudesmentioning
confidence: 79%
“…Limited perceived influence, a sense of not being understood and distress due to uncertainty was described to create a sense of resistance to care. This appeared to have fostered negative beliefs regarding psychiatric inpatient care, which is well recognized [ 44 ] and a known barrier to help-seeking among adolescents with self-harm [ 45 ]. Conversely, being welcomed by professionals with empathy and encouragement, in combination with parental support, was experienced to facilitate the tendency to seek BA in the present study.…”
Section: Discussionmentioning
confidence: 99%